Understanding Burnout in Surgeons: How to Avoid Burnout? - Alam, Mohammed Shadrul (Mugda Medical College Journal, 2024)
Although surgeons work in more stressful medical fields, surgeons are generally considered to offer some of the best lifestyles among physicians. Burnout among surgeons is increasing at an alarming rate. The goals of this review are to increase awareness of the symptoms, causes, and consequences of surgeons’ burnout and how to avoid burnout? Surgeons’ burnout is largely attributed to work-related factors and personal -related factors. Burnout has many potential adverse consequences including professional consequences and personal consequences. The recovery from surgeon’s burnout can take months or longer, therefore it’s important to try to avoid it in the first place through preventative strategies. Mugda Med Coll J. 2023; 6(2): 99-106